Pemberdayaan Ibu Hamil dalam Pencegahan Anemia melalui Edukasi Audio-Visual dan Pendampingan Berbasis WhatsApp Group - Siti Fatimah; Siti Rohmah; Sri Heryani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Anemia in pregnant women is a common health problem that can increase the risk of complications during pregnancy and childbirth. The low level of knowledge among pregnant women regarding the causes, prevention, and management of anemia is a key issue that requires attention. This community service program was carried out in Sukamulya Village, Baregbeg District, Ciamis Regency, as an effort to improve pregnant women’s knowledge and awareness through engaging and easy-to-understand educational activities. Objective: The purpose of this community service activity was to increase pregnant women’s knowledge and awareness of anemia prevention through audio-visual health education and continuous mentoring via a WhatsApp Group in Sukamulya Village Method: This community service activity was conducted in Sukamulya Village through structured education using audio-visual media, followed by interactive mentoring sessions through a WhatsApp Group. Participants were pregnant women from the partner village, and the improvement in knowledge was measured using pre-test and post-test questionnaires. Result: The implementation of the program in Sukamulya Village showed a significant improvement in participants' knowledge. The average pre-test score of 50 increased to 80 in the post-test, resulting in a 48% improvement. Participants also reported a better understanding of anemia risk factors, prevention strategies, and the importance of consuming Iron-Folic Acid (IFA) tablets. Mentoring through the WhatsApp Group enhanced participant engagement and facilitated continuous consultation. Conclusion: The community service program in Sukamulya Village successfully improved pregnant women’s knowledge regarding anemia prevention. The combination of audio-visual education and online mentoring proved to be an effective strategy for community-based health promotion.